Use of Mitomycin-C in Failed Trabeculectomy and High Risk Glaucoma - Memon, Abdul Qadir Shaikh, Muhammad Afzal Pechuho, Syed Imtiaz Ali Shah, Shahid Jamal Siddiqui,Abdul Waheed (Pakistan Journal of Ophthalmology, 2009)
Purpose: To compare the results of simple trabeculectomy with trabeculectomy using Mitomycin–C (MMC) intraoperatively. Material and Methods: This is hospital based descriptive study conducted at the Department of Ophthalmology Chandka Medical College & Hospital Larkana. 50 eyes of 37 patients were selected from glaucoma clinic conducted once a week. After history and complete ocular examination the clinical diagnosis of failed trabeculectomy and high risk glaucoma was established. During the surgical procedure patients were divided into two groups (test group and control group). The twenty five eyes underwent trabeculectomy with Mitomycin-C (MMC) 0.04% for duration of 3 minutes (test group), 25 eyes underwent primary trabeculectomy (control group). Followup period of 6 months was observed in both the groups. The span of study was from January 2006 to December 2007. Results: In this hospital based descriptive study 23 (62.16%) patients were male and 14 (37.83%) patients were female in both groups and mean age of patients in the test group 33.4 years and in control group were 24.4 years. Mean preoperative IOP in the test group was 34.6mmHg (range 20-62mmHg) while in the control group was 30.7mmHg (range 20-45mmHg) and mean postoperative IOP was 17.4 mmHg (range 10-36mmHg) in test group while in control group it was 21.3mmHg (range 11-46 mmHg). Mean IOP lowering was significantly greater in test group than that of control group. Also the number of patients taking adjunctive anti glaucoma medication to control IOP was greater in the control group than in the test group. Conclusion: Mean IOP lowering effect was statistically (P < .05) significantly greater in the test group with the use of MMC intraoperatively.